Language Disorders Faced by Down Syndrome Sufferers at Slb – C Muzdalifah Medan : A Psycholinguistic Analysis - Fauza Pasaribu, Rizka; Lubis, Syahron; Hayati Nasution, Ely (Universitas Negeri Medan, 2024)
This research is a psycholinguistic study which includes an understanding of the language disorders experienced by DS sufferers. This research aimed to find language problems and language disorders experienced by DS sufferers at SLB C Muzdalifah, By using Carroll's theory and the American Speech – Language – Hearing Association. This research used descriptive qualitative methods to answer research problems. The data sources are four students with DS and several teachers at SLB C Muzdalifah Medan. The data in this study was obtained based on the speech of DS sufferers. Based on the analysis conducted it was found that DS sufferers experience two language problems: expressive and receptive language problems, they experience difficulty in constructing sentences, expressing thoughts, limited vocabulary, and understanding complex verbal instructions. Several types of language disorders experienced by DS sufferers are phonological disorders, morphological disorders, syntax disorders, semantic disorders, and pragmatic disorders. Language problems and language disorders cause DS sufferers to experience difficulties in two-way communication.